Phenomic and Genomic Characterization of a Mutant Platform in Cucurbita pepo - García, Alicia; Aguado, Encarni; Parra, Genis; Manzano, Susana; Martínez, Cecilia; Megías, Zoraida; Cebrián, Gustavo; Romero, Jonathan; Beltrán, Sergi; Garrido, Dolores; Jamilena, Manuel (Frontiers in Plant Science, 2018)
The Cucurbita pepo genome comprises 263 Mb and 34,240 gene models organized in 20 different chromosomes. To improve our understanding of gene function we have generated an EMS mutant platform, consisting of 3,751 independent M2 families. The quality of the collection has been evaluated based on phenotyping and whole-genome re-sequencing (WGS) results. The phenotypic evaluation of the whole platform at seedling stage has demonstrated that the rate of variation for easily observable traits is more than 10%. The percentage of families with albino or chlorotic seedlings exceeded 3%, similar or higher to that found in other EMS collections of cucurbit crops. A rapid screening of the library for triple ethylene response in etiolated seedlings allowed the identification of four ethylene-insensitive mutants, that were found to be semidominant (ein1, ein2 and ein3) or dominant (EIN4). By evaluating 4 adult plants from 300 independent families more than 28% of apparent mutations were found for vegetative and reproductive traits, including plant vigor, leaf size and shape, sex expression and sex determination, and fruit set and development. Two pools of genomic DNA derived from 20 plants of two mutant families were subjected to WGS by using NGS methodology, estimating the density, spectrum, distribution and impact of EMS induced mutation. The number of EMS mutations in the genomes of families L1 and L2 was 1,704 and 859, respectively, which represents a density of 11.8 and 6 mutations per Mb, respectively. As expected the predominant EMS induced mutations were C>T and G>A transitions (80.3% in L1, and 61% L2), that were found to be randomly distributed along the 20 chromosomes of C. pepo. The mutations were mostly affecting intergenic regions, but 7.9% and 6% of the identified EMS mutations in L1 and L2, respectively, were located in the exome, and 0.4 and 0.2% had a moderate and high putative impact on gene functions. These results provide information regarding the potential use of the obtained mutant platform in the discovery of novel alleles for both functional genomics and Cucurbita breeding by using direct- or reverse-genetic approaches